ASSESSMENT OF WOMEN’S PARTICIPATION IN MAIZE PRODUCTION IN HAWUL LOCAL GOVERNMENT AREA, BORNO STATE, NIGERIA - Kauna, K.M.; Aliyu, Y.M.; Mudi Z. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study assessed the participation of women maize farmers in Hawul Local Government Area, Borno State. Multi-stage sampling was used to select 290 respondents. Data were collected with structured questionnaires and analyzed using descriptive statistics and regression. Findings show that 53.4% of the respondents earn below ₦100,000 annually and cultivate 1–5 hectares, while 39.3% have 5–10 years of farming experience. Majority (74.1%) of the respondents lack access to credit, and only 25.5% belong to farmer associations. Educational levels were varied, with 33.1% of the respondents attained tertiary education and 28.6% secondary education. Participation was highest in harvesting (90.7%), weeding (86.6%), and land clearing (81.0%). However, fewer women engaged in value addition such as processing (56.2%) and roasting/milling (53.8%), reflecting gaps in post-harvest technology. Regression results showed that income (β = 0.329, p < 0.001), credit access (β = 0.282, p < 0.001), education (β = 0.176, p = 0.001), and association membership (β = 0.178, p = 0.001) significantly influenced participation. The model explained 85% of the variance (R² = 0.85). Major constraints included limited land access (78.6%), financial constraints (83.4%), poor credit access (62.8%), inadequate information (67.9%), pest/disease outbreaks (70.3%), and erratic rainfall (57.9%). Nearly half (49.7%) reported discrimination, and 39.7% experienced theft of produce. Enhancing Access to Credit: This study concludes that women’s participation in maize production in Hawul Local Government Area is substantial and indispensable, but significantly constrained by limited access to financial resources, land, and agricultural support services. Enhancing women’s access to credit, strengthening cooperative membership, and improving their socioeconomic conditions are therefore critical steps toward increasing their productivity and fully harnessing their contribution to maize production in the area. Financial institutions and development organizations should design and implement accessible credit facilities tailored to women farmers. These facilities should feature low-interest rates and flexible repayment terms to encourage adoption and utilization. Capacity Building and Training: Educational programs and vocational training should be developed to improve women’s literacy and technical skills in modern agricultural practices. These initiatives should be implemented through farmer cooperatives, local NGOs, and government extension services to ensure broad participation and impact.